Low-temperature solution-processed high-capacitance AlOx dielectrics for low-voltage carbon-based transistors - Kumar, Ashwini; Perinot, Andrea; Sarkar, Sudipta Kumar; Gupta, Dipti; Zorn, Nicolas; Zaumseil, Jana; Caironi, Mario (Organic electronics, 2022)
Low-temperature processing of high-capacitance metal oxide-based dielectrics by solution-based methods and their application in developing low-voltage carbon-based transistors may enable next-generation low-cost, power-efficient, flexible and transparent electronics. In this work, a high-capacitance AlOx film was developed at a relatively low annealing temperature of ⁓200 °C from its spin-coated precursor solution.
Im Titel erscheint in der chemischen Formel das x tiefgestellt
Gesehen am 29.11.2022